Modlitwa jako narzędzie budowania nowej kultury życia - Derdziuk, Andrzej (Teologia i Moralność, 2018)
Protecting of human life from conception until to natural death is part of the ongoing spiritual struggle between the culture of death and the civilization of love. The destruction of life is the fruit of the negation of God and the attempt to take over the work of creation. The tool in the hands of believers is the prayer that brings man to God and contemplates his work of creation and salvation in Christ and elevating the human person to the dignity of the child of God. The exhortation of the Gospel of life promoted by St John Paul II in the encyclical Evangelium vitae leads to perception of its value and prevents the banishment of human behavior in the face of suffering.